ANALISIS KADAR PARASETAMOL GENERIK DIBANDINGKAN BERMEREK DAGANG - Mariyani; Patala, Recky; Awilia, Nurkhaliza (Universitas Imelda Medan, 2023)
Paracetamol is a substance that can reduce the fever (antipyretic) and relieve the pain (analgesic). Analysis of the levels of generic and branded paracetamol tablets was carried out to determine whether the levels of the active substance in the preparations met the requirements or not by using the High Performance Liquid Chromatography method. The paracetamol quantitative test obtained the results of the levels in sample A = 94.306%, sample B = 99.986%, sample C = 95.296% and sample D = 94.904%. These results indicate that the level of the active substance paracetamol in each sample still meets the requirements of the Indonesian Pharmacopoeia Edition IV, namely not less than 90% and not more than 110%. Statistical analysis using the t-student test, the results of t-count < t-table (0.026 < 2.35) at a significant level of 5%, with the conclusion that there is no significant difference between generic paracetamol and branded paracetamol were analyzed using High Performance Liquid ChromatographyIV, namely not less than 90% and not more than 110%. Statistical analysis using the t-student test, the results of t-count < t-table (0.026 < 2.35) at a significant level of 5%, with the conclusion that there is no significant difference between generic paracetamol and branded paracetamol were analyzed using High Performance Liquid Chromatography.